Manufacturing and Measuring Mechanical Properties of Continuous Functionally Graded Beam - Abbood, Ahmed Mansoor; Mehbes, Haider K.; Hasan, Abdulkareem. F. (Basrah Journal for Engineering Sciences, 2021)
In this study, glass-filled epoxy functionally graded material (FGM) was prepared by adopting the hand lay-up method. The vertical gravity casting was used to produce a continuous variation in elastic properties. A 30 % volume fraction of glass ingredients that have mean diameter 90 µm was spread in epoxy resin ( ρ = 1050 kg/m 3 ). The mechanical properties of FGM were evaluated according to ASTM D638. Experimental results showed that a gradually relationship between Young’s modulus and volume fraction of glass particles, where the value of Young’s modulus at high concentration of glass particles was greater than that at low concentration, while the value of Poisson’s ratio at high concentration of glass particles was lower than that at low concentration. The manufacture of this FG beam is particularly important and useful in order to benefit from it in the field of various fracture tests under dynamic or cyclic loads.